2014
DOI: 10.3171/2014.4.peds13592
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for a giant arteriovenous malformation without motor deterioration: preoperative transcranial magnetic stimulation in a non-cooperative patient

Abstract: Transcranial magnetic stimulation (TMS) is a noninvasive activation method that is increasingly used for motor mapping. Preoperative functional mapping in vascular surgery is not routinely performed; however, in cases of high-grade arteriovenous malformations (AVMs), it could play a role in preoperative decision making. A 16-year-old male was suffering from a giant, right-sided insular, Spetzler-Martin Grade V AVM. This patient's history included 3 hemorrhagic strokes in the past 3 years, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Ille et al ( 188 ) reported their experience of utilizing nTMS to fix the mapping result of fMRI. Kronenburg et al ( 189 ) reported the utilization of TMS to non-cooperative patients and achieved satisfactory results. Although nTMS is widely applied in brain tumors, it has seldom been used for cerebrovascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…Ille et al ( 188 ) reported their experience of utilizing nTMS to fix the mapping result of fMRI. Kronenburg et al ( 189 ) reported the utilization of TMS to non-cooperative patients and achieved satisfactory results. Although nTMS is widely applied in brain tumors, it has seldom been used for cerebrovascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last decade, nTMS has been used by neurosurgeons to map functional areas of the brain for surgical planning in neuro-oncology [5,22], AVM resection [7,9,16], and epilepsy [13]. A successful nTMS depends largely on patient cooperation, with a long duration of the exam and fatigue or discomfort potentially affecting the results of the mapping.…”
Section: Discussionmentioning
confidence: 99%
“…The patient experienced significant dysphasia in the immediate postoperative period which improved by postoperative day 3, with near total resolution by postoperative day 14. nTMS may be a useful modality for noninvasive preoperative functional mapping of speech in patients with AVMs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]…”
mentioning
confidence: 99%